2013
DOI: 10.1088/2041-8205/771/2/l29
|View full text |Cite
|
Sign up to set email alerts
|

Multidimensional Modeling of Coronal Rain Dynamics

Abstract: We present the first multidimensional, magnetohydrodynamic simulations that capture the initial formation and longterm sustainment of the enigmatic coronal rain phenomenon. We demonstrate how thermal instability can induce a spectacular display of in situ forming blob-like condensations which then start their intimate ballet on top of initially linear force-free arcades. Our magnetic arcades host a chromospheric, transition region, and coronal plasma. Following coronal rain dynamics for over 80 minutes of phys… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
102
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(123 citation statements)
references
References 24 publications
18
102
0
3
Order By: Relevance
“…As the coronal rain clumps fall along the loop arcade, they encounter an increasingly more dense atmosphere at the loop foot-points in the TR and on into the chromosphere. The reduced acceleration in the rain has also been observed in quiescent coronal rain (Antolin & Rouppe van der Voort 2012), and this was confirmed numerically to be due to the increase of gas pressure in the lower atmosphere with the greater local densities (Fang et al 2013).…”
Section: Observations Of Flare-driven Coronal Rainsupporting
confidence: 62%
See 2 more Smart Citations
“…As the coronal rain clumps fall along the loop arcade, they encounter an increasingly more dense atmosphere at the loop foot-points in the TR and on into the chromosphere. The reduced acceleration in the rain has also been observed in quiescent coronal rain (Antolin & Rouppe van der Voort 2012), and this was confirmed numerically to be due to the increase of gas pressure in the lower atmosphere with the greater local densities (Fang et al 2013).…”
Section: Observations Of Flare-driven Coronal Rainsupporting
confidence: 62%
“…Radiative losses increase and dominateover conductive losses, and at a later stage a loop-top thermal instability leads to catastrophic cooling (i.e., accelerated cooling) to chromospheric temperatures, and we observe a substantial loop drainage ordepletion, as observed here in Hα. During the thermal instability, the decrease in temperature in the loop is accompanied by a decrease in pressure, which then accretes plasma from the surrounding atmosphere, leading to the localized formation of dense rain condensations (Goldsmith 1971;Hildner 1974;Antiochos & Klimchuk 1991;Müller et al 2004;Fang et al 2013). Clumpy condensations eventually become dense enough to fall under gravity back to the surface (overwhelming the opposing magnetic pressure force of the loop arcade), resulting in a catastrophic depletion of plasma in the loop.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Animated views for the entire simulation in the format of Figure 2 are provided as online material, where the mentioned transverse compressions and their transient nature become evident. From our earlier simulations of actual prominence formation due to chromospheric evaporation, thermal instability, and runaway catastrophic cooling events (Xia et al 2011(Xia et al , 2012Fang et al 2013;, these transient shock waves mimic the rebound shock fronts found to result from siphon flow driven impacts on the prominence-corona transition region. These rebound shocks ultimately repeatedly impact on the prominence structure, as a result of successive reflections when they reach chromospherecorona transition regions along the fieldlines.…”
Section: Global Evolutionmentioning
confidence: 71%
“…Interestingly, the blob leaves a trail (see last four images in the upper panel of Fig. 3), which might be a result of continuous cooling in the blob tails (Fang et al 2013). …”
Section: First Sequence Of Blobsmentioning
confidence: 98%